A fracture mechanics approach to simulate sub-surface initiated fretting wear. (April 2015) - Ghosh, Arnab; Paulson, Neil; Sadeghi, Farshid
Abstract: Sub-surface cracks can be initiated due to surface fatigue, which eventually reach the surface, leading to pitting, spalling and removal of material. In this investigation, a new approach based on shear stress reversal at the crack tips is implemented to propagate a subsurface initiated crack under fretting load. Hertzian line contact geometry is used to investigate the effects of different factors such as Hertzian pressure, coefficient of friction, displacement amplitude, and depth of the initial crack. Crack propagation paths and propagation life of the cracks under the surface are investigated in detail. Once the crack reaches the surface, it is assumed that the material enclosed is spalled and thus removed. Wear volumes and wear rates are calculated and effect of each variable on wear is analyzed. Wear rates increase with increase in maximum Hertzian pressure, displacement amplitude, coefficient of friction and depth of initial crack. The wear rates are also correlated to crack propagation rates and are in agreement with the dissipated energy wear coefficients obtained from literature.